1989
DOI: 10.1161/01.cir.80.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced ST depression in the diagnosis of coronary artery disease. A meta-analysis.

Abstract: To evaluate the variability in the reported diagnostic accuracy of the exercise electrocardiogram, we applied meta-analysis to 147 consecutively published reports comparing exerciseinduced ST depression with coronary angiography. These reports involved 24,074 patients who underwent both tests. Population characteristics and technical and methodologic factors, including publication year, number of electrocardiographic leads, exercise protocol, use of hyperventilation, definition of an abnormal ST response, excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
306
4
22

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(341 citation statements)
references
References 126 publications
9
306
4
22
Order By: Relevance
“…We have chosen generally accepted values based upon large meta analysis studies for the sensitivity and specificity of stress testing. 10,11 With respect to cCTA, there is much controversy in the published literature about the true diagnostic accuracy of the technique. Furthermore, given the rapid pace of technological progress in cCTA, these numbers are constantly improving.…”
Section: Discussionmentioning
confidence: 99%
“…We have chosen generally accepted values based upon large meta analysis studies for the sensitivity and specificity of stress testing. 10,11 With respect to cCTA, there is much controversy in the published literature about the true diagnostic accuracy of the technique. Furthermore, given the rapid pace of technological progress in cCTA, these numbers are constantly improving.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the presence of ST-segment depression with exercise has reasonable sensitivity and specificity for predicting coronary artery disease (22,23). The interpretation of these changes is not reliable when there is electrocardiographic evidence of left ventricular hypertrophy or in patients taking digitalis (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of these changes is not reliable when there is electrocardiographic evidence of left ventricular hypertrophy or in patients taking digitalis (22,23). During adenosine infusion, however, it has been shown that the majority of patients with reversible MPI scans do not have ST-segment depression.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos estudos realizados [8][9][10][11] demonstra sensibilidade entre 50 e 72% (média de 67%) e especificidade entre 69 e 74% (média de 71%). É importante, no entanto, ressaltar as limitações desses valores uma vez que o padrão-ouro de comparação é a cineangiocoronariografia que analisa apenas anatomia da árvore arterial coronariana.…”
Section: I212 -Sensibilidade Especificidade E Valor Preditivounclassified